Social Disclosure Performance as Element of ESG Components in Indonesia’s Banking Companies - Saarce Elsye Hatane; Sherlyn Septyna Santoso; Cynthia Ivana Suseno; Rosalia T. Gabronino (Accounting Department, School of Business and Management - Universitas Kristen Petra, 2025)
This research aims to observe the extent of corporate social performance in the banking sector from four aspects: workforce, human rights, community and product responsibility. To achieve this goal, content analysis was carried out on disclosures related to social performance components in the sustainability reports of six banks with the best ESG performance in Indonesia. Banks in Indonesia concentrate on the management of workforce health and performance, physical and mental health, gender equality, human rights, society and product responsibility. The six banks also prioritised employee welfare, government rights, and community involvement and encouraged education through volunteering, training, and collaboration with the government. Other priorities are product responsibility, maintaining customer data privacy, and ensuring all customer information is secure. This research provides insight into the performance of social element disclosure in ESG of banks in Indonesia, especially the six banks with the best ESG performance.